Comparison of Non-harmonic Vibrational Motion of a Simple Pendulum in Theoretical and Experimental Studies - Khawari, Rajab Ali (Journal of Natural Sciences – Kabul University, 2022)
This paper evaluates the theoretical results of various authors who developed different methods to obtain a simple formula for the period of a simple pendulum's vibration, using experimental data obtained in a physics laboratory. The agreement between the theoretical formulas and the experimental results was well observed. The data acquisition process was based on the accuracy of the optical sensor and protractor, with an error margin of up to 0.1%. Theoretical results were derived through a series of simplifications established at specific intervals, while experimental results determined the accuracy and the applicable range of the formula. The measuring angle ranged from 0 to 85 degrees, in which the pendulum exhibited circular motion. Upon comparing the experimental results with theoretical findings, it was observed that the approximations proposed by Hitt and Carvalhaes & Suppes were more consistent than other approximations and can be accepted as a simple formula for the period of pendulum vibrations at large angles.